Early Warning System in Mobile-Based Impacted Areas - Irvan Moch. Taufiq, Rahadian; Cepy Slamet, Cepy; Andrian, Rian; Aulawi, Hilmi; Ali Ramdhani, Muhammad (International Journal of Engineering and Technology, 2018)
Indonesia is a country prone to earthquake for Indonesia is located between three tectonic plates. Some natural disasters of earthquake caused have a big number of victims. This is due to the ineffectiveness of current early warning system since it still uses conventional way. This study is aimed to create a system that can deliver direct information about earthquake to the people of easy-using mediaand provide direction to the nearest evacuation site to them. Method of system design applies prototype development method. The applied system uses Google Maps API as a tool to trace the userâ€™s location and the evacuation site. In addition, the system will use firebase as a tool of notification delivery.Â Â